Growth performance, haematological changes, immune response, antioxidant activity and disease resistance in rainbow trout (Oncorhynchus mykiss) fed diet supplemented with ellagic acid - Yonar, Serpil Mise (Academic Press Ltd- Elsevier Science Ltd, 2019)
The present study was performed to investigate the effects of various levels of dietary ellagic acid (EA) on growth performance, haematological values, immune response, protection against Yersinia ruckeri infection, and oxidant/antioxidant status in rainbow trout, Oncorhynchus mykiss. Fish were fed with the control diet and three different experimental diets containing three graded levels of EA (50, 100 and 200 mg kg(-1) diet) for 8 weeks. At the end of the experiment, the growth performance [weight gain (WG), specific growth rate (SGR) and feed conversion ratio (FCR)], haematological values [the red blood cell (RBC) count, haemoglobin (Hb) concentration, haematocrit (Ht) level and erythrocyte indices: mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC)1, immune response [white blood cell (WBC) count, oxidative radical production (nitroblue tetrazolium (NBT) assay), phagocytic activity (PA) and phagocytic index (PI), total protein (TP) and immunoglobulin M (IgM) levels, serum bactericidal activity (BA), lysozyme (LYZ) and myeloperoxidase (MPO) activities] and oxidant/antioxidant status [tissue malondialdehyde (MDA) levels and superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) activities] were analysed. In addition, fish were challenged by Y. ruckeri and survival rate was recorded for 14 days. In the groups fed with EA the growth parameters such as WG, SGR, and FCR did not vary significantly. The RBC count, Hb concentration, and Ht level increased in the groups fed with EA when compared with the control group. However, there were no significant differences in the MCV, MCH and MCHC values among the groups. The results demonstrated enhancement in all the immunological parameters in the groups fed with EA compared to the control group. The results obtained from challenge with Y. ruckeri revealed reduction in the mortalities in the groups fed with EA. The dietary EA stimulated the SOD, CAT and GSH-Px activities in liver, head kidney and spleen as compared to the control group; however, a reverse trend was observed in the MDA levels of tissues. The present study suggest that EA can effectively enhance the haematological values, immune response, antioxidant capacity, and disease resistance in rainbow trout.
Keywords: Antioxidant activity; Disease resistance; Ellagic acid; Fish; Growth; Haematology; Immunity; Yersinia ruckeri